DILÂLÂT HURÛF AL-JARR AL-MUTA'ALLIQAH BI AL-AF'ÂL 'INDA AL-ALUSI - Hasyim, Mohamad Yusuf Ahmad (Arabi : Journal of Arabic Studies, 2020)
The semantics of prepositions have special connotations according to the verb followed. It is known that prepositions can reverse the meaning of the verb to the other. The verb becomes more than one meaning because of the different connotation of the preposition by the verb. This research aims to study the semantics of verbs related to prepositions and to highlight the eloquence of the Holy Quran in the diversity of its infringement of the single verb in various prepositions through the study of Alusi interpretation. The method used is a stylistic approach, where researcher collected some verbs related to preposition i. e. adzina-amana-kharaja-h}amala-fa’ala, then analyzed objectively with the extrapolation of the aesthetics of their connotations and suggestions and compare Alusi’s views in his interpretation with former and modern scholars’ interpretations. The result showed that Alusi had both same and different views with former and modern scholars regarding the effect of preposition to the verbs’ meaning.